EVALUATION of INTERCITY PUBLIC TRANSPORT SERVICE QUALITY and PASSENGER PATRONAGE - Ekeugo, Chidiebere; Ikeogu, Christopher; Nwokedi, Theophilus; Ukpere, Wilfred; Monyei, Francis (Journal of Economic Development, Environment and People, 2025)
The study assessed the level of customer satisfaction with the quality of services offered by the main intercity public transport companies on the Owerri-Lagos and Owerri-Abuja travel routes in Nigeria. The study’s objectives were to establish the level of patronage for intercity public transport providers and evaluate the level of service these providers offer on the assigned routes. To collect primary data, a survey instrument called a questionnaire was employed. Utilising the SERQUAL model of service quality, the study assessed respondents’ pre-service and post-service quality expectations and views. Eight key intercity public transport operatives that transport the most intercity passengers through Owerri-Abuja and Owerri-Lagos routes were investigated, in addition to representing the long-distance intercity ways with the topmost demand for intercity journeys from Owerri. The following operators were selected for the study, namely, ABC Transport, LIBRA Motors, Young Shall Grow Motors, Heartland Travels, EKESONS Transport, GUO Transport, CHISCO Transport, and God is Good Motors (GIGM). Descriptive, inferential, and SERQUAL gap models were used to assess the gathered information. The major intercity public transport service operators’ mean coefficient of service quality on the Owerri-Lagos and Owerri-Abuja routes is 23.6%, which suggests that their services are of low quality. However, GIGM received the highest service quality score (31.3%), indicating that individual operators in the sample offer services of disproportionately high quality. Additionally, the findings show that the mean daily patronage (MPAR) of 117.72 people was collected by the operators of intercity public transport services. The analysis also shows a substantial relationship between the amount of demand for intercity travel through specific operators and the quality of intercity public transport services. Individual operators must raise the calibre of their intercity travel services since there is a chance that giving the highest calibre of services and value to clients may increase demand for intercity travel.